Information structure in Nda'nda' - Hugues Carlos Gueche Fotso (Afrika und Übersee)
This paper describes how a syntactic constituent can be manipulated within the structure of a sentence in Nda’nda’ in order to give it pragmatic prominence. To achieve this, attention has to be paid to the various means used by Nda’nda’ speakers to bring listeners to focus their attention on the constituent bearing the special information they want to pass across. Two main categories of prominence in information structure are usually differentiated in language generally: topic and focus. Focus in Nda’nda’ is encoded by cleft constructions, pseudo-cleft constructions and the adverbial ndɑ̀ʔ ‘only’. While analyzing focus via cleft construction we argue that there is similarity between the object cleft construction and the relative clause. The focus marker ndaʔ marks restrictive focus with concomitant morphosyntactic changes. Topic constructions are restricted to noun phrases and are achieved essentially through left-dislocation to mark contrastive topic with an additional pronoun in resumptive function whose form varies depending on whether the topicalized element is human or non-human.